EFFECT OF N- FIXING BIOFERTILIZERS ON GROWTH, YIELD AND QUALITY OF CHILLI (CAPSICUM ANNUUM L.) - S. KHAN; A. PARIARI (The Bioscan, 2012)
To study the effect of inoculation of two nitrogen fixing bacteria culture viz., Azotobacter and Azospirillum with different levels of N (50%, 75% and 100%) in chilli cv. Arka Suphal, an experiment was conducted in the gangetic alluvial plains of West Bengal with sandy loam soil and neutral pH (6.8). Recommended dose of NPK @ 90:60:50 kg/ha and biofertilizer culture @ 500g/ha were applied. Results showed that the inoculation with Azospirillum +75% N alongwith P & K recorded maximum fruit yield (10.25 t/ha), number of fruits/plant (80.20), fruit length (6.72 cm) and oleoresin content (19.80 %). All the growth characters like plant height (62.75 cm) and number of branches/plant (25.15) was found highest with Azospirillum +100% N + PK, which were at par with Azotobacter + 100% N + PK. All the treatments were found superior over control (recommended dose of NPK only). Considering the cost:benefit ratio and yield of the crop, Azospirillum was considered better over Azotobacter.